Transcriptomic analysis of melatonin on the mechanism of embryonic gonadal development in female Jilin white geese - Jin Yu; Ichraf Mabrouk; Qiuyuan Liu; Yuxuan Zhou; Yupu Song; Jingyun Ma; Fengshuo Liu; Xiangman Hu; Zhiyi Yang; Yuxia Zeng; Jingtao Hu; Yongfeng Sun (Poultry Science)
The goose industry represents a significant sector within the broader waterfowl industry in China, with early gonadal development playing a pivotal role in enhancing population productivity. Melatonin plays a crucial role in regulating early gonadal development, but the molecular mechanism underlying the effect of melatonin as a regulator remains unclear. In this study, the relationship between melatonin and egg production performance in Jilin white goose was first established, then, an in Ovo injection of melatonin in goose embryos on the embryonic day 12 (E12) was performed to evaluate the impact of melatonin on the gonadal development in Jilin white goose. The results showed that the in Ovo injection of melatonin increased the expression of FOXL2 in the gonads while decreasing the expression of CYP19A1. Transcriptome analyses revealed that a total of 1184 differentially expressed genes were screened in Jilin white goose embryonic gonads among the two comparison groups. These DEGs were enriched in Gene Ontology (GO) terms related to the microtubule cytoskeleton, cytoskeleton, cell adhesion, and biological adhesion and the KEGG enrichment analysis suggested that the DEGs were mainly enriched in “MAPK signaling pathway”, “Wnt signaling pathway”, “Calcium signaling pathway”, “Focal adhesion”, “Neuroactive ligand-receptor interaction”, “Melanogenesis”, “mTOR signaling pathway”, “ECM-receptor interaction”, and “TGF-beta signaling pathway” in the two comparison groups. The protein-protein interaction network analysis (PPI) indicated that selected DEGs, such as PDIA3, ATCB, PKM, PGAM1, NME2, LDHB, and CALM2, were highly related to the regulation of the reproduction system development. Additionally, the expression trends of 4 identified DEGs were validated by RT-qPCR. In conclusion, this study elucidates the potential regulatory role of melatonin in gonadal development in geese, identifying candidate genes involved in early gonadal differentiation and maturation. Furthermore, the findings offer valuable practical implications for the goose industry, providing professionals with scientifically grounded strategies to enhance reproductive efficiency and overall population productivity.